ANALISIS KINERJA PERANGKAT DESA DALAM PELAYANAN PUBLIK DI DESA SRIKUNCORO KABUPATEN BENGKULU TENGAH - Alexsander; Azuar, Refo; Dodo Sutardi (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
This research was conducted with the aim of: 1) To find out and understand the performance of Srikuncoro village officials in public services, 2) To know and understand the factors that influence public services in Srikuncoro village. The type of research used in this thesis is qualitative research. This research uses descriptive case study techniques, which are carried out intensively, in detail and in depth on the research object. The data in this research was obtained from primary data and secondary data. The data collection techniques used are the observation method, interview method, and documentation method. The data analysis technique is using Data Reduction, Data Display (Data Presentation), and Conclusion Drawing/Verification. The results of this research show that: 1) The performance of Sri Kuncoro Village officials, Central Bengkulu Regency is good, seen from program effectiveness indicators which include: a) Effectiveness indicators, b) Efficiency indicators, c) Productivity indicators, and d) Accountability indicators. 2) Public services provided by Sri Kuncoro Village officials, Central Bengkulu Regency are good, seen from indicators of program effectiveness which include: a) Transparency indicators, b) Participation indicators, and c) Equal rights indicators. 3) The related officials of Sri Kuncoro Village, Central Bengkulu Regency have tried their best to continue to improve the quality of services in Sri Kuncoro Village, Central Bengkulu Regency